ACCOUNTING PROBLEMS OF THE DEPRESSION. - Paton, W. A. (The Accounting Review, 1932)
An extended period of reduced business activity, with its attendant financial difficulties naturally refocuses the attention of accountants on the underlying problems of valuation and income and surplus measurement. One of the questions receiving increased attention is the old problem of the distinction between operating costs and non-operating charges or losses. In times of depression such as the present, it is noticeable that many business managements, in their desperate anxiety to make a showing, are waking up to the fact that there is some basis for drawing a line between operating charges and non-operating losses. It is the business of the accountant to preserve every legitimate distinction, to bring out every angle of the situation that has a vital bearing from the point of view of any interest concerned, but it is also his business, as far as lieth in him, to see that no improper use be made of this approach to the treatment of business transactions and their results. Operating costs are charges which can be logically imputed to the regular activities of the enterprise during a particular period.